Digital Natives and Sharia Economic Education: Millennial and Gen Z Learning Preferences in the Digital Era (Al Irfan : Jurnal Ilmu Pendidikan dan Penelitian, 2025)
Millennials and Gen Z, who are often referred to as digital natives because of their high skills in using technology, have unique expectations for digital experiences, including in the field of education, especially sharia economic education. This article aims to explore how a technology-based approach can increase the effectiveness of Islamic economics learning for these two generations, who tend to prioritize personalization, interactivity, and connection with relevant values. With a focus on learning strategies that integrate sharia values ​​such as sustainability, justice and inclusivity, this research highlights the role of advanced technologies such as artificial intelligence (AI) and big data in designing learning experiences that suit the needs and characteristics of this generation. In addition, this article also identifies opportunities and challenges in implementing technology to support sharia economic education that is not only academically relevant, but also makes a real contribution to the formation of a more inclusive and sustainable society. The resulting insights are expected to provide practical guidance for educators, policy makers and technology developers in creating innovative learning ecosystems suited to the digital era.